Complementary, Alternative, and Other Noncomplete Decongestive Therapy Treatment Methods in the Management of Lymphedema: A Systematic Search and Review. Issue 3 (18th September 2013) - Rodrick, Julia R.; Poage, Ellen; Wanchai, Ausanee; Stewart, Bob R.; Cormier, Janice N.; Armer, Jane M.
Abstract : Objectives: (1) To provide a critical analysis of the contemporary published research that pertains to complementary, alternative, and other noncomplete decongestive therapies for treatment of lymphedema (LE), and (2) to provide practical applications of that evidence to improve care of patients with or at risk for LE. Type: This study meets the defining criteria as a systematic search and review because it includes varied study types. All studies that met the inclusion criteria were evaluated for weight of evidence and value. Literature Survey: The systematic search and review includes articles published in the contemporary literature (2004‐2012). Publications published from 2004‐2011 were retrieved from 11 major medical indices by using search terms for LE and management approaches. Literature archives were examined through 2012. Data extraction included study design, objectives pertaining to LE, number and characteristics of participants, interventions, and outcomes. Study strengths and weaknesses were summarized. Study evidence was categorized according to the Oncology Nursing Society Putting Evidence into Practice level‐of‐evidence guidelines after achieving consensus among the authors. No authors participated in development of nor benefitted from the review of these modality methods or devices. Methodology: Extracted data from 85 studies were reviewed in 4 subcategories: botanical, pharmaceutical, physical agent modality, and modalities of contemporary value. After review, 47 articles were excluded, which left 16 articles on botanicals and pharmaceuticals and 22 articles for physical agent modality and/or modalities of contemporary value. Pharmaceuticals were later excluded. The authors concluded that botanicals had generated sufficient studies to support a second, more specific systematic review; thus, botanicals are reported elsewhere. Synthesis: It was found that limited high‐level evidence was available for all categories. Well‐constructed randomized controlled trials related specifically to LE were limited. Objective outcome measures over time were absent from several studies. The rationale for the use and benefits of the specific modality, as related to LE, was often anecdotal. Subject numbers were fewer than 50 for most studies. Conclusions: No interventions were ranked as "recommended for practice" based on the Putting Evidence into Practice guidelines. Two treatment modalities in 3 studies were ranked as "likely to be effective" in reducing LE or in managing secondary LE complications. Consideration should be given that many of the PAMs demonstrate long‐standing support within the literature, with broad parameters for therapeutic application and benefit for secondary conditions associated with LE. However, further investigation as to their individual contributory value and the factors that contribute to their efficacy, specific to LE, has not been done. It also is significant to mention that the majority of these studies focused on breast cancer–related LE. Studies that explored treatment interventions for LE‐related vascular disorders (eg, chronic venous insufficiency, congenital dysphasia, trauma) were sparse. Limitations of the literature support the recommendations for future research to further examine the level of evidence in these modalities for LE management.